2014
DOI: 10.3109/00498254.2014.914600
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effects of extracts of vinegar-baked Radix Bupleuri and saikosaponins on the activity of cytochrome P450 enzymesin vitro

Abstract: 1. In this article, the modulatory effects of extracts from vinegar-baked Radix Bupleuri (VBRB) and saikosaponins on the activity of CYP1A2, CYP2C9 and CYP3A4 were investigated in vitro. 2. Microsomal in vitro incubation method was utilized to simulate metabolic reaction under physiological environment by incubating the marker with liver microsomes in the absence or presence of VBRB and saikosaponins. The contents of 4-acetamidophenol, 6β-hydroxyltestosterone and 4-hydroxydiclofenac, the metabolites of phenace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…A previous study demonstrated Bupleurum and vinegar-baked Bupleurum had strong induction effects on CYP2D6 in rats, 38 while our results indicated that SsD plays an important role in the induction effect of CYP2D6, which may be one of the imperative factors for Bupleurum and vinegar-baked Bupleurum in that it can induce the CYP2D6 enzyme. For CYP1A2, SsD has been reported to have a slight inhibition effect as a compromise to its induction effect in rat-liver microsomes, 39 while our study indicated that SsD can significantly induce CYP1A2, probably owing to the fact that when the activity of CYP enzymes was measured through microsomal in vitro incubation, the actual concentration of substrate available to them depends on processes missing in subcellular models, covering transport mechanisms, cytosolic enzymes, and intracellular protein binding, while intact cells can better simulate the disposal environment of drugs in the liver. 40 Disadvantages of the liver microsomal drug-metabolism model in vitro include but are not limited to destruction of the complete structure during the preparation process and aspecific reactions being more likely to occur in the in vitro incubation system and the lack of a complete enzyme-reaction system being required for metabolism, which needs to have the right amount of NADPH added.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated Bupleurum and vinegar-baked Bupleurum had strong induction effects on CYP2D6 in rats, 38 while our results indicated that SsD plays an important role in the induction effect of CYP2D6, which may be one of the imperative factors for Bupleurum and vinegar-baked Bupleurum in that it can induce the CYP2D6 enzyme. For CYP1A2, SsD has been reported to have a slight inhibition effect as a compromise to its induction effect in rat-liver microsomes, 39 while our study indicated that SsD can significantly induce CYP1A2, probably owing to the fact that when the activity of CYP enzymes was measured through microsomal in vitro incubation, the actual concentration of substrate available to them depends on processes missing in subcellular models, covering transport mechanisms, cytosolic enzymes, and intracellular protein binding, while intact cells can better simulate the disposal environment of drugs in the liver. 40 Disadvantages of the liver microsomal drug-metabolism model in vitro include but are not limited to destruction of the complete structure during the preparation process and aspecific reactions being more likely to occur in the in vitro incubation system and the lack of a complete enzyme-reaction system being required for metabolism, which needs to have the right amount of NADPH added.…”
Section: Discussionmentioning
confidence: 99%
“…Drug distribution is often affected by metabolism enzymes and drug transporters. Previous studies have shown that VBRB inhibits cytochrome p450 enzymes (CYP) 3A3 and CYP2D6 [ 25 ], partly explaining its liver-targeting effects. However, a previous study also demonstrated that VBRB increases the liver distribution of the oxymatrine metabolite, indicating that metabolism enzymes are not the only mechanism by which VBRB exerts its liver-targeting effects.…”
Section: Discussionmentioning
confidence: 99%
“…BC1, mainly containing polysaccharides, had the effect of regulate and enhance immunity [21]. BC3 was mainly composed of low molecular weight water soluble components [22], no reports were found on its pharmacological effects and needed further study. BC2 was mainly composed of saponins which were also the main and bioactive components of VBRB [2224], so we investigated the saponins to seeking the main active compounds of VBRB in follow-up experiment.…”
Section: Discussionmentioning
confidence: 99%
“…BC3 was mainly composed of low molecular weight water soluble components [22], no reports were found on its pharmacological effects and needed further study. BC2 was mainly composed of saponins which were also the main and bioactive components of VBRB [2224], so we investigated the saponins to seeking the main active compounds of VBRB in follow-up experiment. The results showed that the native saponins (saikosaponin a, c, d) decreased, and the secondary saponin (saikosaponin b 2 ) increased gradually with the increasing proportion of vinegar.…”
Section: Discussionmentioning
confidence: 99%